Problem psikologis danstrategi coping pada pelaksana upacara adat rambu solo’tana’ bulaan miskin di dusun pambalan - Jeanri Rara Mille Kety; Krismi Diah Ambarwati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
Tana Toraja is a unique area where its customs are very well known, one of which is the solo sign (traditional death ceremony), although the consequences are not good it can even cause psychological problems, such as stress, anxiety, depression and other effects, until now there are still many perpetrators tana' bulaan who are still trying to perform the traditional signs ceremony solo' in accordance with the tradition that applies to family members who die. This study aims to find out psychological problems and how coping strategies are used by the performers of the traditional signs ceremony in tana'bulaan impoverished. The research design uses a qualitative phenomenological method. Collecting data using observation and interview techniques. The sample in this study were 2 participants who were selected by snowball or chain sampling with the characteristics of the Toraja people who perform the traditional ceremonies for signs solo', tana'bulaan, poor in Pambalan Village. The results of the study show that there are several themes involved in psychological problems and coping strategies, including the view of the solo sign, that the solo sign is a custom that must be preserved and is the final tribute to family or relatives who have died. It was also found that there was a stress reaction because of the solo signs. Stress coping strategies, where there are several coping strategies for the two participants such as cognitive assessment, emotional focused coping, and problem focused coping. Protection factors against stress include social support, preparation and planning. As well as found risk factors for stress, such as lack of emotional expression and lack of self-acceptance.